Trends and characteristics of primary pyogenic spine infections among people who do and do not inject drugs: Northeast New York State, 2007 to 2018. (June 2022) - Sola, Steven; O'Connor, Casey; Farry, Leigh A.; Roddy, Kristina; DiRisio, Darryl; Dufort, Elizabeth M.; Robbins, Amy; Tobin, Ellis
Background: Pyogenic spine infections (PSIs) are challenging to diagnose and treat. People who inject drugs (PWID) are at increased risk and contribute to rising PSI incidence. Objective: To analyze trends and characterize PSI in persons who do and do not inject drugs in northeast New York State (NYS), a predominantly rural region. Methods: A retrospective study of PSI patients at a regional tertiary care hospital from 2007 to 2018 was conducted. PSI incidence, population demographics, microbiology, surgical interventions, length of stay (LOS), and costs were compared between injection substance use disorder (ISUD) and non-ISUD cohorts. Results: Two hundred and seventy patients (59 ISUD and 211 non-ISUD) were included in this study. PSI incidence due to ISUD increased 1175% during the study time periods. The median age of the ISUD and non-ISUD cohorts was 39 and 65, respectively. Staphylococcus aureus was the most common causative organism, although a variety of bacterial and fungal pathogens were identified. Nearly half of the patients in each cohort required surgical intervention. Median acute care LOS was 12 days and comparable between cohorts. However, the ISUD cohort was frequently discharged against medical advice, or transferred back to acute care hospitals to complete antibiotic courses. Median inpatient hospital costs were approximately $25, 000 and were comparable between cohorts. These costs do not reflect inpatient costs once the patient was transferred back to the referring hospital, nor costs for outpatient care. Medicaid and Medicare were the most common primary insurance payers for the ISUD and non-ISUD cohorts, respectively. Conclusions: Incidence of PSI has increased significantly coincident with the opioid epidemic and has had significant impact on a large, rural region of NYS. PSIs consume large amounts of healthcare resources. This study can inform hospitals and public health agencies regarding the need for substance abuse harm reduction strategies.